2017
DOI: 10.1007/s10980-017-0497-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation and spatial scale dependency of ecosystem service interactions: a case study on the central Loess Plateau of China

Abstract: Contexts An important feature of ecosystem service interaction is that it changes over time and across spatial scales. Objectives This research aims to find which ecosystem service interactions temporally vary and depend on spatial scale. Methods We calculated six ecosystem services of the Baota District on the central Loess Plateau of China for 2000, 2005, and 2010. Furthermore, we quantified the interactions among these services at the beginning and after the end of the first phase of the Grain for Green Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Several studies have shown that interactions among ecosystem services can be dependent of the scale of observation (e.g. Anderson et al 2009;Raudsepp-Hearne and Peterson 2016;Hou et al 2017). Likewise, we found that the severity of the trade-off between timber production and carbon storage, as indicated by the steepness of the production possibility curves, was affected by the spatial scale of the planning region.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have shown that interactions among ecosystem services can be dependent of the scale of observation (e.g. Anderson et al 2009;Raudsepp-Hearne and Peterson 2016;Hou et al 2017). Likewise, we found that the severity of the trade-off between timber production and carbon storage, as indicated by the steepness of the production possibility curves, was affected by the spatial scale of the planning region.…”
Section: Discussionsupporting
confidence: 61%
“…This finding highlights the likely need for ecological monitoring beyond forest cover changes when considering positive co-benefits and ecological outcomes from PES programs. The recognition that CFC may not serve as a robust proxy for ecological metrics is important as GTGP has been suggested to increase biodiversity based on habitat quality models driven by land use and land cover (Hou et al 2017). Our analyses in FNNR demonstrate that higher forest cover may not translate into higher plant or wildlife species biodiversity gains.…”
Section: Forest Cover: An Unreliable Biodiversity Proxymentioning
confidence: 79%
“…In fact, they provide many ecological, sociocultural, and economic benefits for society that include the following: regulating services, such as water cycling regulation or control and mitigation of extreme climatic events; provisioning services, such as grazing, wood-fuel or medicinal plants; and cultural services, zsuch as traditional knowledge or cultural identity (Körner et al 2005;Foggin 2016). Over time, ecosystem processes that support ecosystem services may be affected by land use changes and the associated land cover changes (Reyers et al 2009) ultimately impacting on benefits for society and human well-being (Ciftcioglu 2017;Hou et al 2017;Sonter et al 2017). Each particular land cover change might lead to a variation in the potential supply (i.e., the hypothetical maximum yield of a service that can be provided by natural components of the ecosystem without the intervention of stakeholders; Geijzendorffer et al 2015) of multiple ecosystem services (Vallet et al 2016).…”
Section: Introductionmentioning
confidence: 99%